2019
DOI: 10.1111/chd.12778
|View full text |Cite
|
Sign up to set email alerts
|

Too little too late? Communication with patients with congenital heart disease about challenges of adult life

Abstract: Objective To investigate the experiences and communication preferences of adult patients with congenital heart disease (CHD) in the domains of employment, insurance, and family planning. Design Patients ≥ 18 years of age completed a questionnaire about experiences and communication preferences regarding employment, health insurance, and family planning. Results Of 152 patients (median age = 33 years, 50% female, 35% with CHD of great complexity), one in four reported work‐related problems due to CHD and a quar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…There is limited prior work looking specifically at the insurance status of pregnant women with CHD. While prior studies report issues of insurability for adults with CHD, including self-reported gaps in coverage, 19,20 the current study as well as other reviews of national databases have shown very low rates of self-pay/uninsured status. 2,3 It may be that pregnancy becomes a motivating factor for women with CHD to maintain or re-establish insurance coverage.…”
Section: Discussionmentioning
confidence: 51%
“…There is limited prior work looking specifically at the insurance status of pregnant women with CHD. While prior studies report issues of insurability for adults with CHD, including self-reported gaps in coverage, 19,20 the current study as well as other reviews of national databases have shown very low rates of self-pay/uninsured status. 2,3 It may be that pregnancy becomes a motivating factor for women with CHD to maintain or re-establish insurance coverage.…”
Section: Discussionmentioning
confidence: 51%
“…A recent study of adult women with CHD demonstrated that the vast majority reported being sexually active, with the median age of first sexual encounter being 18 years old. 26 However, just around half reported having conversations with their provider about reproductive health and a high percentage in this study reported unplanned pregnancies. 26 Our results in an adolescent population echo the finding of limited conversations and also show that a high percentage of adolescents and mothers favour having conversations about reproductive health in the early teen years.…”
Section: Discussionmentioning
confidence: 64%
“…26 However, just around half reported having conversations with their provider about reproductive health and a high percentage in this study reported unplanned pregnancies. 26 Our results in an adolescent population echo the finding of limited conversations and also show that a high percentage of adolescents and mothers favour having conversations about reproductive health in the early teen years. This is supported by an American Heart Association statement suggesting initiating conversations about reproductive health in adolescents with CHD at 12 years of age, if developmentally appropriate.…”
Section: Discussionmentioning
confidence: 64%
“…Transition aged and Hispanic ACHD of all ages were more uninsured than the rest of the ACHD population in all time periods. For transition aged patients, this may be due to feeling well, not understanding the need for ongoing follow-up, low healthy literacy, changing from a pediatric to an adult care system, and/or the logistical challenges of being personally responsible for obtaining health insurance for the first time (Clarizia et al, 2009;Cooley et al, 2011;Crowley, Wolfe, Lock, & McKee, 2011;Deng et al, 2019;Fegran, Hall, Uhrenfeldt, Aagaard, & Ludvigsen, 2014;Gurvitz et al, 2013;Lopez et al, 2015). For Hispanic patients, lack of access to appropriate ACHD care, immigration status, language barriers, and/or cultural differences may present additional challenges.…”
Section: Discussionmentioning
confidence: 99%